The lives of Agnes Smedley - Price, Ruth, 1951- (OUP E-Books., 2005)
"Was she a selfless political activist? A feminist heroine? A gifted writer who rose from poverty to become a leading journalist and author of the cult classic Daughter of Earth? A spy for the Soviet Union? Or all of these things?" "Drawing on fifteen years of intensive research and unprecedented access to previously unpublished documents, this book brings to life one of the twentieth century's most fascinating women. Ruth Price traces Agnes Smedley's unlikely trajectory from a small Missouri town to the coal country of Colorado; to Berkely and Greenwich Village; to Berlin, Moscow, and China. Fueled by a fury at injustice, Smedley threw herself headlong into the crucial issues of the time, from Indian independence to birth control, women's rights, and the revolution in China. Her friends included such figures as Margaret Sanger, Langston Hughes, Emma Goldman, Jawaharlal Nehru, Mao Zedong, and many others. Perhaps most important, Price uncovers an astonishing truth: Smedley, long thought to be the unfair target of a Cold War smear campaign, was indeed guilty of the espionage charges leveled against her by General Douglas MacArthur and others. Smedley worked to foment armed revolution in India and gathered intelligence for the Soviet Union, seeing it as a bulwark against fascism. Price argues that Smedley acted out of a passionate idealism and that she exhibited a courage and compassion worthy of a renewed, if more complicated, admiration today."--Jacket